Oral health service utilization by elderly beneficiaries of the Mexican Institute of Social Security in México city - Solórzano-Santos Fortino; Mendoza José; Reyes-Morales Hortensia; Juárez-Cedillo Teresa; de la Fuente-Hernández Javier; Sánchez-García Sergio; García-Peña Carmen (BMC, 2007)
Abstract Background The aging population poses a challenge to Mexican health services. The aim of this study is to describe recent oral health services utilization and its association with socio-demographic characteristics and co-morbidity in Mexican Social Security beneficiaries 60 years and older. Methods A sample of 700 individuals aged 60+ years was randomly chosen from the databases of the Mexican Institute of Social Security (IMSS). These participants resided in the southwest of Mexico City and made up the final sample of a cohort study for identifying risk factors for root caries in elderly patients. Sociodemographic variables, presence of cognitive decline, depression, morbidity, medication consumption, and utilization of as well as reasons for seeking oral health services within the past 12 months were collected through a questionnaire. Clinical oral assessments were carried out to determine coronal and root caries experience. Results The sample consisted of 698 individuals aged 71.6 years on average, of whom 68.3% were women. 374 participants (53.6%) had made use of oral health services within the past 12 months. 81% of those who used oral health services sought private medical care, 12.8% sought social security services, and 6.2% public health services. 99.7% had experienced coronal caries and 44.0% root caries. Female sex (OR = 2.0), 6 years' schooling or less (OR = 1.4), and caries experience in more than 22 teeth (OR = 0.6) are factors associated with the utilization of these services. Conclusion About half the elderly beneficiaries of social security have made use of oral health services within the past 12 months, and many of them have to use private services. Being a woman, having little schooling, and low caries experience are factors associated with the use of these services.